Analysis of MUI Fatwa Number 17 of 2020 Regarding Kaifiat Prayer Guidelines for Health Workers Who Wear Personal Protection Equipment (PPE) When Treating and Handling Covid-19 Patients - Oktalita, Frina; Rizki, Darlin (Institut Agama Islam Negeri Curup, 2021)
This study aims to analyze the MUI fatwa no. 17 of 2020 concerning the guidelines for prayer for health workers who wear personal protective equipment (PPE) when handling and caring for COVID-19 patients. This study tries to describe the ijtihad method used by MUI in establishing a law. This study uses a type of library research with descriptive analysis. The results of this study state that health workers (PPE) must continue to pray even though it’s not possible to purify themselves (ablution or tayamum). With consideration, 1) if the body (lahiriyah) in hadas condition, it is not obligate his pray (I'adah), 2) if the PPE is unclean then it is necessary to repeat the prayer. The fatwa cannot be separated from the syar'i argument which is the basis for issuing the fatwa, particularly using the talfiq manhaji method. The fatwa can be used as an alternative to confusion over the law, and is intended to create benefits, especially for health workers who treat and handle Covid-19 patients.